Family Literacy Parenting Strategies Supporting Children During Preschool to Primary School Transition - Fono, Yasinta Maria; Ngura , Elisabeth Tantiana; Wea, Ludgardis (Jurnal Prima Edukasia, 2025)
The transition from Early Childhood Education (or PAUD in the Indonesian context) to elementary school is a pivotal stage where children shift from "learning to read" to "reading to learn." This study examines the role of family parenting styles in enhancing children's literacy skills during this critical phase. Utilizing a qualitative phenomenological approach, the research explores parents’ lived experiences in supporting the development of reading and writing at home. Data were collected through in-depth interviews, participatory observations, and documentation, then analyzed using thematic analysis. The findings indicate that democratic parenting styles significantly foster children’s intrinsic motivation and independence in literacy. Key practices, such as intensive verbal interactions, dialogic reading, and post-reading discussions, were found to enhance comprehension, narrative skills, and expressive language. Furthermore, purposeful digital media use, combined with active parental mediation, supports multimodal literacy development. Consistent reading routines and strong emotional involvement were identified as vital supporting factors, while limited parental time and a lack of age- appropriate materials emerged as primary barriers. The study concludes that family parenting is a decisive factor in bridging literacy gaps during the transition to elementary school. This research contributes to the literacy transition discourse by establishing a multifaceted family literacy framework specifically tailored for the transition from PAUD to primary schooling. These findings imply the necessity for a family literacy model that integrates democratic parenting, rich verbal interaction, and guided digital literacy to ensure children are prepared for increasing academic demands.